Collagen matrix as an inlay in endoscopic skull base reconstruction. Issue 3 (18th July 2017) - Oakley, G M; Christensen, J M; Winder, M; Jonker, B P; Davidson, A; Steel, T; Teo, C; Harvey, R J
Abstract: Background: Multi-layer reconstruction has become standard in endoscopic skull base surgery. The inlay component used can vary among autografts, allografts, xenografts and synthetics, primarily based on surgeon preference. The short- and long-term outcomes of collagen matrix in skull base reconstruction are described. Methods: A case series of patients who underwent endoscopic skull base reconstruction with collagen matrix inlay were assessed. Immediate peri-operative outcomes (cerebrospinal fluid leak, meningitis, ventriculitis, intracranial bleeding, epistaxis, seizures) and delayed complications (delayed healing, meningoencephalocele, prolapse of reconstruction, delayed cerebrospinal fluid leak, ascending meningitis) were examined. Results: Of 120 patients (51.0 ± 17.5 years, 41.7 per cent female), peri-operative complications totalled 12.7 per cent (cerebrospinal fluid leak, 3.3 per cent; meningitis, 3.3 per cent; other intracranial infections, 2.5 per cent; intracranial bleeding, 1.7 per cent; epistaxis, 1.7 per cent; and seizures, 0 per cent). Delayed complications did not occur in any patients. Conclusion: Collagen matrix is an effective inlay material. It provides robust long-term separation between sinus and cranial cavities, and avoids donor site morbidity, but carries additional cost.